The first freedom : the tumultuous history of free speech in America - Hentoff, Nat. (New York : Delacorte Press, 1988)
A history of free speech in our country from earliest times to some of the controversial court cases of today involving school demonstrations and the right of Nazis to march.
Includes index.
Bibliography: p. 347-353.
Keywords: Freedom of speech -- United States -- History -- Juvenile literature; Freedom of speech -- History